iSpeak public speaking for contemporary life - Nelson, Paul E.|q (Paul Edward) 1941-; Titsworth, Scott; Pearson, Judy C. (Boston McGraw-Hill Higher Education, 2009)
Preparing your presentations; Selecting and arranging content; Types of presentations
Rev. ed. of: Public speaking. 2007.
Includes bibliographical references and index.
Keywords: Public speaking; Diễn thuyết